(untitled) (AYUSHDHARA, 2024)
Motherhood is beautiful reflection. It indeed encompasses a deep sense of creation, not just in the physical sense, but in nurturing life, fostering growth, and shaping futures. Abortion incidence in India it is estimated that 15.6 million abortions take place per year. Abortion either medical or criminal has distinctive physical, social, and psychological side effects. Ayurveda emphasizes the Physicians’ obligations during pregnancy, from conception to postpartum care Centrality of topic: Garbha "Chalana" means "to move" or "displacement," and it also means "to indicate fetus." According to Ayurveda, Garbha Chalana is a situation in which the fetus shifts from its normal position. Ayurvedic texts recommend treating this disease on a monthly basis. This indicates that the fetus is unstable, irregularly lodged in the womb, and exhibiting quivering or other aberrant motions might occur every month. Acharya Harita mentions Garbha Chalana Chikitsa. However, the classics also describe month-by-month treatment for this condition, suggesting that it is probably a Prasramsamana Garbha condition, which means that the fetus starts to descend slightly for expulsion, and that there is pain and burning in the back and flanks, as well as excessive bleeding, abdominal distension, and urine retention. The purpose of monthly Garbha Chalana treatments and various formulations is to stabilize the fetus from the overall treatment approach is aimed at conserving energy, ensuring proper nourishment and promoting the healthy despite the complications the focus is on creating a conductive environment within the body for the fetus to thrive through up to 8th month and beyond.